Comparative Development of Multiple Seedlings in Different Seed Sources of Azadirachta indica A. Juss - Singh, S. L.; Banerjee, A. C.; Shukla, N. K.; Burfal, B. S.; Mishra, C. M.; Dubey, P. (Indian Forester, 2001)
The occurrence of multiple seedlings were observed in Neem (Azadirachta indica) during the germination studies in different Seed Sources of seeds. In the case of Neem the emergence of multiple seedlings is not due to polyembryony but due to sowing of seeds along with the endocarp of fruit not kernel. Each endocarp encloses 1-4 seeds in it. However, in the present study it differs in different Seed Sources.